A study of motivations and expectations of patients seen in phase 1 oncology clinics. Issue 22 (26th September 2016) - Dolly, Saoirse O.; Kalaitzaki, Eleftheria; Puglisi, Martina; Stimpson, Sarah; Hanwell, Janet; Fandos, Sonia Serrano; Stapleton, Sarah; Ansari, Thushara; Peckitt, Clare; Kaye, Stan; Lopez, Juanita; Yap, Timothy A.; et al.
Abstract : BACKGROUND: To better inform clinical practice, this study was aimed at capturing patients' motivations for enrolling in phase 1 trials and at quantifying their expectations of the benefits, risks, and commitment associated with clinical trials and the impact of the initial consultation on their expectations. METHODS: This was a single‐center, prospective, quantitative study of newly referred adult patients considering their first phase 1 oncology trial. Participants completed questionnaires before they were seen and an abbreviated follow‐up version after their consultation. RESULTS: Questionnaires were completed by 396 (99%) and 301 (76%) before and after the clinic, respectively. Participants ranked the possibility of tumor shrinkage (84%) as the most important motivation for considering a phase 1 trial; this was followed by no alternative treatments (56%), their physician's recommendation (44%), and the fact that the research might benefit others (38%). When they were asked about the potential personal benefit, 43% predicted tumor shrinkage initially. After the consultation, this increased to 47%. Fourteen percent of patients expected a cure. When asked about risks, 71% of the participants expected moderate side effects. When asked about expectations of time commitments, a majority of patients did not anticipate weekly visits, although this was understood by 93% of patients after the consultation. Overall, patients were keen to consider trials and when asked before and after the consultation 72% and 84% were willing to enroll in studies, respectively. CONCLUSIONS: This study reports that more than 80% of patients enroll in early‐phase clinical oncology trials motivated by the potential of a clinical benefit, with approximately half expecting tumor shrinkage and approximately a tenth anticipating a cure. The typical phase 1 response rate is 4% to 20%, and this discrepancy exemplifies the challenges faced by patients and healthcare professionals during their interactions for phase 1 studies. Cancer 2016;122:3501–3508 . © 2016 American Cancer Society Abstract : More than 80% of patients seen in phase 1 oncology clinics are willing to participate in studies, with approximately half hoping for tumor shrinkage, and approximately a tenth anticipating a cure. These exceed realistic response rates of 4% to 20%, and the initial phase 1 consultation does not alter the majority of expectations except for an understanding of the time commitment involved.